Interstitial Cells of Cajal (ICC) and Gastrointestinal Stromal Tumor (GIST): facts, speculations, and myths - Min, K. W.; Leabu, M. (Journal of cellular and molecular medicine, 2006)
Interstitial cells of Cajal (ICC) is a peculiar cell network composed of cells having processes described by the eminent Spanish neuroanatomist of the 19th century, S. Ramon y Cajal. ICC became a fascinating subject to many investigators and it is estimated that there are over 100 publications yearly on the subject related to ICC, in the last three years. Now it is widely accepted that ICC are pace maker cells of the gut and probable progenitor cells of gastrointestinal stromal tumors (GIST). Lately, interstitial Cajal‐like cells (ICLC) are being found in various organs and their physiological role is still to be defined. We have reviewed the literature trying to evaluate the validity of the current concept and found that there are a few salient points to be considered. 1) There has been some important departure in defining the identity of ICC from the original criteria of Cajal. In particular, ICC with myoid feafures in intestinal smooth muscle layers (ICC‐DPM) do not seem to fit to the original description of interstitial cell network by Cajal. We have also pointed out that the current reports assigning a pace maker role to ICC vastly depend on the scientific data on “ICC with myoid features”, not on “fibroblast‐like ICC”, which are more abundant and easier to identify. 2) There seem to be an overwhelming amount of data proving the relationship between ICC and GIST. Both are known to express c‐Kit and the ultrastructural characteristics seen in GIST roughly parallel those of ICC including minimal myoid differentiation seen in the majority of GIST, supporting the current concept that GIST are ICC tumors. 3) According to the original description of Cajal, ICC was not limited to the gut, suggesting an existence of ICC in other organs. The list of organs reported to contain ICC (currently identified by immunohistochemistry and electron microscopy) is ever growing and further studies are needed to define their identity and pathophysiologic role. 4). Recent data concerning gut development suggest that both c‐Kit expressing ICC (fibroblasts‐like as well as muscle‐like) and gut muscle cells derive from the common progenitor cells of the embryonic gut unifying the histogenetic concept of all GIST with heterogeneous cytomorphologic features. In this review we attempted to incorporate recent information on interstitial Cajal‐like cells (ICLC) found in other organs to broaden our understanding of ICC in general in terms of their ultrastructure, physiology, and neoplasia.